Postgraduate Researcher Special Issue: Editorial - Thomas, Michael; Goulding, John; Patrick, Mireille (PRISM: Casting New Light on Learning, Theory and Practice, 2022)
This special edition of PRISM brings together seven papers authored by postgraduate research students arising from the 1st International Doctoral Research Conference in Education hosted by the Centre for Educational Research (CERES) at Liverpool John Moores University on 8th July 2020. Over 500 participants registered for this fully online event delivered via videoconferencing from over 17 different countries, just as the first of our several lockdowns were occurring throughout the world due to the COVID-19 pandemic.